Investing in Young Children : An Early Childhood Development Guide for Policy Dialogue and Project Preparation - Naudeau, Sophie; Kataoka, Naoko; Valerio, Alexandria; Neuman, Michelle J.; Elder, Leslie Kennedy (World Bank, 2012)
Investing in young children is the responsible thing to do. All children deserve a chance to grow into healthy, educated, and competent people, no matter where and when they were born. While parents bear most of the responsibility for raising their children, especially in the early years of life, governments also have an important role during this critical time of human capital accumulation. For example, governments can ensure that all expectant mothers and young children have access to quality health services and nutrition. They can support parents and other caregivers in providing a positive and stimulating environment for children from birth on by promoting parenting information programs, investing in direct services such as home-based visits, funding daycare centers and preschools, or providing financial incentives to access good quality programs for infants and children. This Early Childhood Development (ECD) guide presents lessons and experiences that have been useful in informing the policy debate about ECD interventions and the design of such programs across the world. Whether the user of this guide is at the initial stage of deciding whether to expand an ECD portfolio or already in the program design stage, the content offers a range of evidence- based options to inform policy and investment choices.